PENGEMBANGAN LEMBAR KEGIATAN SISWA DENGAN PENDEKATAN STRATEGI PENEMUAN KONSEP PADA MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - HIDAYATI, NURUL (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Learning in biology requires students to understand the concepts. One way to engage students in finding the concept is to use teaching materials. As in the matter of biodiversity requires more than simply memorizing understanding. Therefore, the necessary teaching materials that assist students in finding the concept. The purpose of this research is to generate worksheets with the invention of the concept of strategic approach to biodiversity material, describes the theoretical and empirical feasible with the student worksheet approach concept discovery strategy on biodiversity materials. The type of this research is development research, namely the development of worksheets with concept discovery approach strategy on biodiversity materials. The research is done based on 4-D.In this research, development procedure is only done in the development stage. The definite experiment is dome at tenth grade Al-Islam Krian Sidoarjo Senior High School with twenty four students. The result of this research indicates that student worksheet based on guided discovery which is developed, can be declared viable theoritical and empirical. The theoritical feasible is observed by validation result namely 86,66% to 91,68% with category very viable and the empirical feasible is observed by response of student after doing learning with student worksheet that be developed namely 86%. Keywords: student worksheet, concept discovery, biodiversity.